2022
DOI: 10.3329/jbcbm.v7i1.57124
|View full text |Cite
|
Sign up to set email alerts
|

Commercially available organic manures on growth, yield and nutrient content of Burmese Grapes (Baccaurea ramiflora)

Abstract: A pot experiment was carried out in the net house of the Department of Soil, Water and Environment, University of Dhaka to evaluate the effectS of different organic manures on the growth performance, biomass production, NPKS content in leaf, stem and root of Burmese grapes (Baccaurea ramiflora) and some chemical properties of post- harvest soil. Two-month old Burmese grapes seedlings were planted in different organic manure-treated soils (viz. ACI, BGF, Bhola, Green Life, Kazi, Modern, Mazim, Payel, Payel Eart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Nonetheless, if the organic manure companies are to be compared, Kazi treated plants showed poor growth performance, which has been supported by low nutrient accumulation (3.96 mg plant -1 ) in their leaves, despite the fertilizer having relatively higher contents of N, P, K, S and Fe among other fertilizer companies. However, a study conducted on Burmese grapes with organic manures reported that Kazi and Payel are preferred for healthy and strong growth of the seedlings (Munna et al 2021). In our study, the overall good growth performance was recorded in Naafco treated plants, with the highest nitrogen and sulphur accumulation in their leaves.…”
Section: Nutrient Uptakesupporting
confidence: 50%
See 1 more Smart Citation
“…Nonetheless, if the organic manure companies are to be compared, Kazi treated plants showed poor growth performance, which has been supported by low nutrient accumulation (3.96 mg plant -1 ) in their leaves, despite the fertilizer having relatively higher contents of N, P, K, S and Fe among other fertilizer companies. However, a study conducted on Burmese grapes with organic manures reported that Kazi and Payel are preferred for healthy and strong growth of the seedlings (Munna et al 2021). In our study, the overall good growth performance was recorded in Naafco treated plants, with the highest nitrogen and sulphur accumulation in their leaves.…”
Section: Nutrient Uptakesupporting
confidence: 50%
“…Every day, around 16,500 tonnes of wastes are produced in cities, if processed properly can create an excellent opportunity to meet the rising need of organic fertilizers (Howlader 2017). Several studies conducted on the effects of the application of organic manures such as poultry manure, cow dung, mustard oil cake, vermicompost and other composts, have recorded increases in growth and yield of vegetables, such as red amaranth (Mondal et al 2019, Alam et al 2007) and okra (Haque et al 2020), Burmese grapes (Baccaurea ramiflora) (Munna et al 2021), mint (Mentha sp.) (Shushupti et al 2021), and have also found improved quality of leafy vegetables.…”
Section: Introductionmentioning
confidence: 99%